Implementing tuberculosis preventive treatment in high-prevalence settings. (December 2021) - Fox, Greg J.; Nguyen, Thu Anh; Coleman, Mikaela; Trajman, Anete; Velen, Kavindhran; Marais, Ben J.
Highlights: Tuberculosis preventive treatment is effective and feasible in high-prevalence settings. Successful scale-up of tuberculosis preventive treatment requires attention to all steps in the 'cascade of care'. The greatest drop-out typically occurs prior to commencement of therapy. Programs should adopt a patient-centred approach. Shorter-course regimens promise to improve treatment completion. Operational research can help to localise the use of preventive therapy. Abstract: Latent tuberculosis infection affects one quarter of the world's population, and effective therapies are available. However, scale-up of tuberculosis preventive treatment (TPT) remains limited. We describe strategies to support scale-up of TPT in high-prevalence settings, where the potential benefit for affected individuals is considerable. Patients must be at the centre of policies to scale-up TPT. Addressing the health system requirements for scale-up will ensure that programs can deliver treatment safely, efficiently and sustainably. Further research is required to adapt TPT to local contexts, and develop new shorter treatments that will be suitable for wide-scale deployment.